TRAINING ON MAKING PURPLE SWEET POTATO STICKS IN COT CUT VILLAGE, KUTA BARO DISTRICT, ACEH BESAR: PELATIHAN PEMBUATAN STICK UBI UNGU DI DESA COT CUT KECAMATAN KUTA BARO ACEH BESAR - Ika Rezvani Aprita; Suraiya Nazlia; Suri Purnama Febri; Irmayanti; Putri Meutia Sari; Virna Muhardina; Kurnia; Mulyanti; Muhammad Afdal; Endiyani; Maghfirah; Irhami; Chairil Anwar; Sri Agustina; Indra Akbar (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The abundant availability of purple sweet potatoes in Cot Cut Village at a very low price is the backdrop for this community service activity. The processing of purple sweet potatoes into value-added products is expected to increase the added value of this commodity. The purpose of this community service activity is to provide homemakers in Cot Cut Village with training in making purple sweet potato sticks. Socialization, training, and direct practice of making purple sweet potato sticks are the methods used in this community service. The results of this community service indicate that the community has gained knowledge of the purple sweet potato processing process, which can increase product competitiveness. Processing purple sweet potatoes into sticks is a strategy to increase the independence and economic welfare of the Cot Cut Village community in the Aceh Besar Regency.